Fabrication and characterization of anti-microbial and biofouling resistant nanofibers with silver nanoparticles and immobilized enzymes for application in water filtration - Du Plessis, Danielle Marguerite (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2011.